Europium Fluorescent Nanoparticles-Based Multiplex Lateral Flow Immunoassay for Simultaneous Detection of Three Antibiotic Families Residue - Wang, Yaping; Ma, Biao; Liu, Miaomiao; Chen, Erjing; Xu, Ying; Zhang, Mingzhou (Frontiers in Chemistry, 2021)
A fluorescent immunoassay based on europium nanoparticles (EuNPs-FIA) was developed for the simultaneous detection of antibiotic residues, solving the problems of single target detection and low sensitivity of traditional immunoassay methods. In the EuNPs-FIA, EuNPs were used as indictive probes by binding to anti-tetracyclines monoclonal antibodies (anti-TCs mAb), anti-sulphonamides monoclonal antibodies (anti-SAs mAb) and anti-fluoroquinolones monoclonal antibodies (anti-FQs mAb), respectively. Different artificial antigens were assigned to different regions of the nitrocellulose membrane as capture reagents. The EuNPs-FIA allowed for the simultaneous detection of three classes of antibiotics (tetracyclines, fluoroquinolones and sulphonamides) within 15 minutes. It enabled both the qualitative determination with the naked eye under UV light and the quantitative detection of target antibiotics by scanning the fluorescence intensity of the detection probes on the corresponding detection lines. For qualitative analysis, the cut-off values for tetracyclines (TCs), fluoroquinolones (FQs) and sulphonamides (SAs) were 3.2 ng/mL, 2.4 ng/mL and 4.0 ng/mL, respectively, which were much lower than the maximum residue limit in food. For quantitative analysis, these ranged from 0.06 to 6.85 ng/mL for TCs, 0.03 to 5.14 ng/mL for FQs, and 0.04 to 4.40 ng/mL for SAs. The linear correlation coefficients were higher than 0.97. The mean spiked recoveries ranged from 92.1% to 106.2% with relative standard deviations less than 8.75%. Among them, the three monoclonal antibodies could recognize 4 types of TCs, 7 types of FQs and 13 types of SAs, respectively, and the detection range could cover 24 antibiotic residues with different structural formulations. The results of the detection of antibiotic residues in real samples using this method were highly correlated with those of HPLC (R^2 > 0.98). The accuracy and precision of the EuNPs-FIA also met the requirements for quantitative analysis. These results suggested that this multiplex immunoassay method was a promising method for rapid screening of three families of antibiotic residues.